Przemiany polityczne w wybranych krajach Europy w latach 1985-1991 i ich wpływ na integrację kontynentu = The political changes in the years 1985-1991 in selected European countries and their impact on the integration of the continent - Kromych, Grzegorz; Rabant, Hubert (Journal of Education, Health and Sport, 2015)
Kromych Grzegorz, Rabant Hubert. Przemiany polityczne w wybranych krajach Europy w latach 1985-1991 i ich wpływ na integrację kontynentu = The political changes in the years 1985-1991 in selected European countries and their impact on the integration of the continent. Journal of Education, Health and Sport. 2015;5(12):50-63. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34882 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A50-63 http://pbn.nauka.gov.pl/works/676006 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015. Przemiany polityczne w wybranych krajach Europy w latach 1985-1991 i ich wpływ na integrację kontynentu The political changes in the years 1985-1991 in selected European countries and their impact on the integration of the continent Kromych Grzegorz, Rabant Hubert Instytut Geografii, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie: Artykuł omawia przemiany polityczne w Europie w latach 1989-1991. Do analizy wybrane zostały trzy kraje: byłe ZSRR, Polska oraz Niemcy. Wskazano najważniejsze wydarzenia polityczne, które umożliwiły demokratyzację tego obszaru. Omówiony zostały także wpływ tych przemian na możliwości integracji europejskiej. Abstract: The article discusses the political changes in Europe in the years 1985-1991. Three countries: the former Soviet Union, Poland and Germany were selected to the analysis. There were pointed the main political events that enabled to the democratization process of the area. Also the impact of these changes on the European integration was discussed. Słowa kluczowe: przemiany polityczne, Europa, integracja Europy. Keywords: political changes, Europe, the European integration.